Men's sexual and reproductive health in the situation of HIV-serodiscordance - Tassiane Ferreira Langendorf; Stela Maris de Mello Padoin; Ivis Emília de Oliveira Suza (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to know men's perspective in face of reproduction in the situation of HIV-serodiscordance. Method: qualitative study developed in a university hospital in Southern Brazil. Unstructured in-depth interviews were conducted with 11 men living with HIV and a thematic content analysis was performed. Results: men expressed not wanting to have children and that this pregnancy was different. They showed concerns related to the vertical transmission of HIV, sexual and reproductive rights and responsibility in the exercise of parenthood. Final considerations: men's perspective is influenced by their role in the family, which is historically and culturally determined, and by the concerns about infection, which are socially determined and entail their understanding of reproductive rights and their participation in care. In services, men's perspective must be considered in the planning and implementation of health care actions by supporting their participation in the exercise of fatherhood.